2014
DOI: 10.11604/pamj.2014.18.319.2242
|View full text |Cite
|
Sign up to set email alerts
|

Le décollement épiphysaire fémoral supérieur post infectieux, à propos de deux cas

Abstract: Le décollement épiphysaire post infectieux est une pathologie très rare, jamais décrite dans la littérature. Nous rapportons deux cas colligés au service: le 1er concerne un garçon âgé de 3 ans, admis pour impotence fonctionnelle du membre inferieur droit. La radiographie a objectivé un glissement de l’épiphyse fémorale supérieure par rapport à la métaphyse avec un épanchement échogène intra articulaire à l’échographie. Une artrotomie avec drainage ont été réalisé, puis le malade a été mis sous antibiothérapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Staphylococcus aureus is the causative organism in more than 90% of cases, due to its capacity to adhere to cartilage [15]. Radiographs show epiphyseal detachment, periosteal reaction or pathological fracture [10]. In our case, we found an associated sub-trochanteric pathological fracture.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Staphylococcus aureus is the causative organism in more than 90% of cases, due to its capacity to adhere to cartilage [15]. Radiographs show epiphyseal detachment, periosteal reaction or pathological fracture [10]. In our case, we found an associated sub-trochanteric pathological fracture.…”
Section: Discussionmentioning
confidence: 56%
“…Septic hip arthritis in children remains a grave clinical problem in the developing world due to its association with delayed diagnosis, resulting complications and their disabling sequelae. Septic detachment of the hip is a rare complication [6,10]. A few authors have reported unilateral cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations